Trazodone in the treatment of chemical addictions - A. R. Asadullin; E. A. Akhmetova; I. S. Efremov; K. A. Gasenko; R. R. Borukaev; I. V. Kolyvanova; E. M. Krupitsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2025)
Trazodone is an FDA-approved antidepressant used to treat depression. However, mental health professionals also use it to treat various psychiatric and medical conditions, including substance use disorders, which have FDA- not approved indications. The problem of addiction to these substances is an important part of modern psychiatric care. Among all the risk factors for premature death, tobacco use ranks second, while alcohol use ranks seventh. Direct exposure to these substances and their negative health effects contribute significantly to premature mortality. Thus, the issue of proper treatment for disorders associated with their use remains important and relevant. Trazodone has been shown to have antagonistic effects on serotonin receptors (5-HT2) and is also a serotonin reuptake inhibitor. It has been demonstrated to be effective in individuals with alcohol, benzodiazepine, and opiate addictions, as well as other dependencies. Although the exact mechanism of trazodone’s action in the body has not been fully understood, its advantage lies in its relatively low number of side effects compared to other medications. Despite this, trazodone may be a suitable option for improving depressive symptoms and sleep issues in patients, potentially reducing the risk of relapsing into substance abuse.